Test and evaluation method for endurance performance of electric multi-rotors spraying drones - Ming, Rui; Zhou, Zhiyan; Luo, Xiwen; Lan, Yubin; He, Xingang; Song, Cancan; Jiang, Rui; Tian, Luhong; Hassan, Shahbaz Gul (International Journal of Agricultural and Biological Engineering, 2019)
The endurance performance (EP) of electric multi-rotors spraying drones (EMSDs) is a key technical indicator that ensures the completion of tasks and improves their usefulness. To improve the EP of current EMSD, a test system was designed to determine the EP based on the EMSD test platform, and the performance evaluation method was studied. Firstly, a test model was established to determine the equivalent energy dissipation using the performance-testing platform of the EMSD. Secondly, a multisensory test system was constructed. An attitude sensor, high-power DC power supply, infrared thermal imager, and serial port server were selected. The mounting fixture was designed to meet the universal mounting requirements of drone. In addition, the software LabVIEW was employed to program the code for the controller and the host computer, where functions such as data collection, data processing, communication, and graphical user interface (GUI), were performed reliably in real time. Thirdly, the test method was explored by considering factors such as the power consumption, thermal efficiency ratio, and unit load power consumption rate. In particular, a comprehensive index method and expert consultation weight method were used to evaluate the EP of the EMSD with multiple indexes. Finally, a systematic real-machine test was carried out on the three types of drones that are currently widely used in the market. The results verified the effectiveness and feasibility of the proposed method, which was employed to test and evaluate the EP based on the EMSD performance testing platform. At the same time, it can provide a reference for the development of the EMSD.Keywords: agricultural aviation, multi-rotors spraying drone, endurance performance, assessment method, virtual instrumentDOI: 10.25165/j.ijabe.20191202.4348Citation: Ming R, Zhou Z Y, Luo X W, Lan Y B, He X G, Song C C, et al. Test and evaluation method for endurance performance of electric multi-rotors spraying drones. Int J Agric & Biol Eng, 2019; 12(2): 18–28.